Effect of UV and water spraying on the mechanical properties of flax fabric reinforced polymer composites used for civil engineering applications. (15th April 2015) - Yan, Libo; Chouw, Nawawi; Jayaraman, Krishnan
Graphical abstract: Highlights: UV weathering degraded mechanical properties of flax/epoxy composites. SEM confirmed degradation in fibre/matrix interfacial bonding. UV weathering caused discolouration, matrix erosion, microcracking. Abstract: The lack of data related to durability is one major challenge that needed to be addressed prior to the widespread acceptance of natural fibre reinforced polymer composites for engineering applications. In this work, the combined effect of ultraviolet (UV) radiation and water spraying on the mechanical properties of flax fabric reinforced epoxy composite was investigated to assess the durability performance of this composite used for civil engineering applications. Specimens fabricated by hand lay-up process were exposed in an accelerated weathering chamber for 1500 h. Tensile and three-point bending tests were performed to evaluate the mechanical properties. Scanning electron microscope (SEM) was used to analyse the microstructures of the composites. In addition, the durability performance of flax/epoxy composite was compared with synthetic (glass and carbon) and hybrid fibre reinforced composites. The test results show that the tensile strength/modulus of the weathered composites decreased 29.9% and 34.9%, respectively. The flexural strength/modulus reduced 10.0% and 10.2%, respectively. SEM study confirmed the degradation in fibre/matrix interfacial bonding after exposure. Comparisons with other composites implies that flax fabric/epoxy composite has potential to be used for civil engineering applications when taking its structural and durability performance into account. Proper treatments to enhance its durability performance will make it more comparable to synthetic fibre reinforced composites when considering as construction building materials.